Assessing adoption intention of electric vehicles in India: The mediating role of government policies - Joshi, Nitin; Malhotra, Meenakshi; Singh, Jashandeep (European Journal of Transport and Infrastructure Research, 2022)
The total number of vehicles is expected to be 2.5 billion by the year 2050. To stabilize the impact on environment, the automobile sector has shown various innovations by shifting from conventional vehicles to electric vehicles (EVs). However, there is less acceptance of electric cars in India, so this research paper explores the various factors affecting EV adoption intention. The key factors studied are price, environmental concern, infrastructure requirement, and knowledge of EV. This paper also shows that government policies act as a mediator between factors like price, knowledge of EV, and infrastructure requirement on adoption intention of EVs. This research paper presents insights for the decision-makers to understand the determinants and design the strategies for increased adoption intention of EVs.